Partial characterization of Maize rayado fino virus isolates from Ecuador: Phylogenetic analysis supports a Central American origin of the virus - Chicas Romero, Mauricio (2007)
Maize rayado fino virus (MRFV) infects maize and appears to be restricted to, yet widespread in, the Americas.MRFVwas previously unreported from Ecuador. Maize plants exhibiting symptoms of MRFV infection were collected at the Santa Catalina experiment station in Quito, Ecuador. RT-PCR reactions were performed on total RNA extracted from the symptomatic leaves using primers specific for the capsid protein (CP) gene and 3  non-translated region of MRFV and first strand cDNA as a template. Nucleotide sequence comparisons to previously sequenced MRFV isolates from other geographic regions revealed 88–91% sequence identity. Phylogenetic trees constructed using Maximum Likelihood, UPGMA, Minimal Evolution, Neighbor Joining, and Maximum Parsimony methods separated the MRFV isolates into four groups. These groups may represent geographic isolation generated by the mountainous chains of the American continent. Analysis of the sequences and the genetic distances among the different isolates suggests that MRFV may have originated in Mexico and/or Guatemala and from there it dispersed to the rest of the Americas